Assessing the efficacy of Kenya's international and national obligations in enhancing the effective political participation of persons with disabilities (PWDs) in Kenya - Muasya Kasema, Roy Michael (Department of Philosophy, 2025)
The overall objective of this research is to examine the effectiveness of Kenya's legal frameworks (including the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD), Constitution of Kenya (CoK) and Persons with Disabilities Act (PDA)) that condition the political participation of persons with disabilities (PWDs)1, and to explore the extent to which, consequently, PWDs do and can exercise their participatory rights2. Based on a desktop-study, using primarily secondary literature and qualitative evidence, this study observed that, despite Kenya's broad legal framework in support of the full inclusion of PWDs in political activities, the same has not been effectively realized. It also assesses why, despite the adoption of these seemingly progressive laws, PWDs have struggle to fully actualize their political rights. It is evidenced that, in some areas, there are gaps and shortfalls in the statutes thereby derogating PWDs' rights and submitting them to, as opposed to protecting them from, exclusion and marginalization in Kenya. Furthermore, there is a shortage in reasonable accommodations and measures to foster an environment conducive to PWDs effectively engaging in politics in Kenya. This, coupled with the underrepresentation of PWDs in decision-making, militates against, instead of promoting the exercise of their political rights in Kenya. Therefore, a lot more needs to be done to ensure that PWDs can fully and effectively participate in political affairs in Kenya.